Cognitive Development and Academic Achievement Extent of Association - A Review Report - Marwaha, Shruti; A. K. Sinha; Ramesh Sahani (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2019)
Education, cognition and learning have become integral part of every child’s personality. These inseparable aspects are considerably vital in shaping the individual and helping him to achieve success. In the schools and educational institutes where education has been taken on priority, the cognitive abilities and excellence in mastering them mitigate the burdens and stress in educational system. In this context, it is assumed that when the children are taught as per their affinity and dominant multiple intelligence, they can learn better and turn into efficient learners. This review paper has been written in order to compile the augmented knowledge into systematic and scientific information to ensure that the educational processes can become lucid for masses. The valid studies related to cognitive development including intelligence quotient, focus factor, decision making ability, creative quotient and academic achievement in light of multiple intelligences were selected. The review studies have been taken on international basis for universal application. It was inferred after the review that the concept of teaching students through multiple intelligences approach should be adopted to make create a meaning and impactful teaching learning process.